Elemen Liberal Dalam Kajian Fikih Di Pesantren : Studi Atas Ma'had Aly Salafiah Syafi'iyah Sukorejo Situbondo - Musahadi, Musahadi (UIN Sunan Kalijaga, 2013)
This research is aimed at answering a big question on the dynamic of Islamic legal studies in Islamic boarding school (pesantren) through focusing on the study of fiqh in Ma’had Aly. The research questions were formulated into two points. First, how far the liberal elements has coloured the Islamic legal studies in Ma’had Aly. Second, why the liberal ideas emerge inpesantren milieu that is well-known as an orthodoxy defender in Islamic law and has strong commitment to the doctrine of salaf as-??li?.The collection of data in this research was conducted through the studies on the written documents, observation, interviews, and simple questionnaire for check and recheck purpose. The analysis basically was undertaken by descriptive technique in qualitative method. The findings of the research showed that the Islamic legal studies in Ma‘had Aly Situbondo is strongly nuanced by liberal elements either in the level of epistemology of the study that they developed or in the level of praxis of the studies. There are some reasons why the study on Islamic Law at the Ma’had Alyis very strongly coloured with liberal elements, i.e.: 1) the turning stream of intellectual urbanisation-dissemination emerged within the Ma‘had Aly; 2) The dissatisfaction among the community of Ma‘had Aly on the epistemology of fiqh of NU; 3) inspiration brought about by the figure of liberalism thinkers both classic and modern, local and global; 4) the existence of historical reference on liberal ideas of NU; 5) the factor of open mindedness of teachers (pengasuh); and 6) the factor of networking of Ma‘had Aly with NGOs, study centers, and other liberal epistemic community.